(untitled) (Journal of Face Aesthetics, 2025)
This review paper was written as a part of continuing medical education/self-education, aimed to draw the attention of clinicians, particularly medical youth, to the fact that diseases with a predilection for the face not only fall within the scope of aesthetic medicine but also include potentially lethal diseases. Hence, it is important to differentiate these diseases at the clinical level. In the case of pemphigus group bullous diseases, a physical examination of cardinal importance for the diagnosis, namely naming the lesions and their locations ("what and where"), should enable the clinician to choose the appropriate laboratory diagnostic procedures. Therefore, laboratory methods of diagnosing pemphigus diseases were critically evaluated here.